What Makes Firms Grow in Developing Countries? An Extension of the Resource-Based Theory of Firm Growth and Empirical Analysis - Lee, Keun; Temesgen, Tilahun (2012)
This paper examines what makes firms grow using the investment climate survey that was conducted by the World Bank in eight developing countries. We rely on the resource-based theory of the firm that was proposed by Penrose (1959) where firm growth depends on the kinds and amount of the diverse resources a firm has. The paper extends Penrose's original idea to accommodate diverse options for firm growth and finds the following. First, in low-growth (capability) firms, growth is contributed by basic resources such as physical capital and human capital, whereas in high-growth firms, by higher-level resources such as managerial capital and research and development (R&D) capital. Second, the difference between low- versus high-growth firms has more to with the effectiveness of the relevant resources and less with the difference in the amount of resources. Third, export orientation and conglomeration are the most important strategies for firm growth, compared to networking with other local, state-owned enterprises (SOEs) or foreign firms.